Bioefficacy of a microemulsified mangosteen peel extract formulation against fruit rot fungi - Mohd Zainudin, Nur Ain Izzati; Azmi, Nur Haliah Munifah; Abdul Rahman, Mohd Basyaruddin; Asmawi, Azren Aida (Nature Research, 2026)
This study presents a microemulsion-based biopesticide formulation incorporating Garcinia mangostana L. (mangosteen) peel extract for the control of fruit rot diseases caused by fungal pathogens. Mangosteen peel is rich in bioactive compounds such as xanthones and flavonoids, which exhibit potent antifungal properties. The microemulsion is prepared using a phase inversion composition (PIC) method, incorporating virgin coconut oil (VCO) as the oil phase and Tween 80 as the surfactant, resulting in a stable and homogenous oil-in-water system. The optimized formulation consisted of 0.20% (w/w) mangosteen peel crude extract, 4.80% VCO, 5.00% Tween 80, 1% α-tocopherol, and distilled water to complete 100% (w/w) of the composition. The formulation exhibited significant antifungal activity both in vitro and in vivo against Fusarium oxysporum, Fusarium proliferatum, and Colletotrichum gloeosporioides, pathogens responsible for fruit rot in crops such as banana, tomato, and mango. The microemulsion, ME80% effectively inhibited fungal growth, spore germination, and significantly reduced disease severity in treated fruits. The enhanced antifungal efficacy is attributed to the synergistic action of phytochemicals present in the extract, highlighting the potential of this formulation as a sustainable and eco-friendly alternative for fruit rot disease management.